2019
DOI: 10.1093/hmg/ddz097
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen enhances synaptic function and neural progenitors proliferation markers and improves neuropathology and motor coordination in Machado–Joseph disease models

Abstract: Machado–Joseph disease or spinocerebellar ataxia type 3 is an inherited neurodegenerative disease associated with an abnormal glutamine over-repetition within the ataxin-3 protein. This mutant ataxin-3 protein affects several cellular pathways, leading to neuroinflammation and neuronal death in specific brain regions resulting in severe clinical manifestations. Presently, there is no therapy able to modify the disease progression. Nevertheless, anti-inflammatory pharmacological intervention has been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Thus, we cannot exclude that trehalose effects might occur, or at least count with contribution of indirect effects in peripheral energy metabolism and inflammatory pathways [55,56]. Therapeutic strategies that improves metabolism energy and inflammation, such as caloric restriction [22] and ibuprofen [57], are indeed effective in MJD mouse models. Interestingly, trehalose can also affect gut microbioma [58] , which raise the hypothesis that trehalose might interfere by modulating the microbiota-gut-brain axis.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we cannot exclude that trehalose effects might occur, or at least count with contribution of indirect effects in peripheral energy metabolism and inflammatory pathways [55,56]. Therapeutic strategies that improves metabolism energy and inflammation, such as caloric restriction [22] and ibuprofen [57], are indeed effective in MJD mouse models. Interestingly, trehalose can also affect gut microbioma [58] , which raise the hypothesis that trehalose might interfere by modulating the microbiota-gut-brain axis.…”
Section: Discussionmentioning
confidence: 98%
“…The non-steroidal anti-inflammatory drug ibuprofen [37] has also been examined in SCA3/MJD models and shown to improve neuropathology and motor coordination concomitant with reductions in the neuroinflammatory markers interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and phosphorylated IKB-α. Ibuprofen has been examined in clinical trials for AD and found to reduce delta rhythm progression in mild cases [89].…”
Section: Inhibition Of Inflammationmentioning
confidence: 99%
“…Ibuprofen, on the other hand, is maybe the most popular non-steroidal anti-inflammatory drug, used in the treatment of many musculoskeletal disorders [11], and is the safest traditional choice for utilization during chronic neuroinflammation such as in Alzheimer's [12], Parkinson's [13], and Machado-Joseph disease [14]. Hybrids of ibuprofen with quinoline are interesting [11] in order to study their potential biological Likewise, the 1,2,3,4-tetrahydroquinoline skeleton is prevalent in many pharmacologically active synthetic and natural products [9].…”
Section: Introductionmentioning
confidence: 99%